The Smart Mobility Concept by Developing Online-Based Transportation Information and Communication Technology for Sustainable Transportation - Djajasinga, Nico Djundharto (STMIK Dharma Wacana, 2022)
The advancement of communication technology is rather quick, resulting in societal changes. Many companies have begun to emerge as a result of communication technology advancements, one of which is the introduction of intelligent transportation in the form of online-based transportation services. People can better evaluate which mode of transportation is best for their mobility requirements by integrating transportation services with information and communication technologies. This study was carried out in order to identify smart transportation through the advancement of information technology and online-based transportation communication. This research employs a descriptive qualitative technique in which the author attempts to describe, analyze, and construct meaning regarding existent occurrences. The study's findings indicate that combining transportation services with the use of information and communication technology causes major changes in people's social lives, particularly in the usage of transportation for activities. Internet transportation combines the most recent transportation advancements with online communication technology to deliver community convenience. To order transportation online at any time and from any location. The Smart Mobility concept can be applied to online transportation, particularly online motorcycle taxis like Go-Jek and Grab a bike, by utilizing categories, indicators, and parameters tailored to the development of Online Ojeks, such as accessibility, sustainability, and information technology systems.